2013
DOI: 10.11648/j.ajpn.20130102.11
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thiamine in Autism

Abstract: Autism spectrum disorders are a group of neuro-developmental conditions characterized by varying degrees of language impairment, including verbal and non-verbal communication, impaired social skill, and repetitive behaviors. In this paper, we review the evidence for an association between autism and thiamine. A relationship between thiamine status and the development of autism has been established, with thiamine supplementation exhibiting a beneficial clinical effect on children with autism. Thiamine may invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 161 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…A number of hypotheses have been put forward on the pathophysiological mechanisms linking thiamine deficiency and ASD (135), including i) increased apoptosis, due to the link of thiamine with p53 (136, 137), Bcl-2 (138, 139), and caspases (140); ii) deregulation of the serotoninergic system (141, 142); and iii) increased oxidative stress, due to the putative role of thiamine in prostaglandin expression, decreased lipid peroxidation as well as expression of nitric oxide synthase (143, 144), and its involvement as a cofactor for TKT in the PPP, master regulator of NADPH homeostasis.…”
Section: Pathology Of Thiamine Deficiencymentioning
confidence: 99%
“…A number of hypotheses have been put forward on the pathophysiological mechanisms linking thiamine deficiency and ASD (135), including i) increased apoptosis, due to the link of thiamine with p53 (136, 137), Bcl-2 (138, 139), and caspases (140); ii) deregulation of the serotoninergic system (141, 142); and iii) increased oxidative stress, due to the putative role of thiamine in prostaglandin expression, decreased lipid peroxidation as well as expression of nitric oxide synthase (143, 144), and its involvement as a cofactor for TKT in the PPP, master regulator of NADPH homeostasis.…”
Section: Pathology Of Thiamine Deficiencymentioning
confidence: 99%
“…Nerve cells are a major source of cutting high-energy demand; thiamine promotes energy production and protects cells from oxidative stress. 72 Additionally, thiamine and its derivatives control the production of acetylcholine, receptor function, cholinergic neurotransmission, and antioxidant and neurotrophic effects in the brain. 73 Animal studies have shown that reduced prenatal and postnatal thiamine intake affects the developing brain of newborn rats and that the memory of rats raised by thiamine-deficient dams is impaired.…”
Section: Thiamine (B1)mentioning
confidence: 99%
“…Nerve cells are a major source of cutting high-energy demand; thiamine promotes energy production and protects cells from oxidative stress. 72 Additionally, thiamine and its derivatives control the production of acetylcholine, receptor function, cholinergic neurotransmission, and antioxidant and neurotrophic effects in the brain. 73…”
Section: Vitamin Bmentioning
confidence: 99%
“…It was, also, linked with Alzheimer's disease (AD) after the appearance of plaques and β-amiloid in animal models [50]. The implication of thiamine in ASD can be seen via its effects on apoptotic factors (factor p-53, caspase-3, and Bcl-2), oxidative stress (prostaglandins, reactive oxygen species, nitric oxide synthase, mitochondrial dysfunction) and neurotransmitter systems (serotonin, glutamate, and acetylcoline) [51].…”
Section: Thiamine (Vitamin B 1 )mentioning
confidence: 99%